2016
DOI: 10.1097/igc.0000000000000566
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Diagnosis Support Tool for Serous Ovarian Tumors Based on Microarray Data Using Multicategory Machine Learning

Abstract: We identified 2 biomarkers, SNTN and AOX1, that are likely involved in the pathogenesis and progression of ovarian tumors. An accurate diagnosis of ovarian tumor subclasses by application of the equation in conjunction with expression analysis of SNTN and AOX1 would offer a new accurate diagnosis tool in conjunction with frozen-section diagnosis within 30 minutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…For example, loss of AOX1 expression by epigenetic regulation could promote bladder cancer via metabolic deregulations; the SNP rs73055188 of AOX1 locus is related to prostate cancer survival time, and AOX1 gene expression level is correlated with recurrence of prostate cancer [44]. However, the roles for AOX1 in ovarian cancer have not been addressed [45]. In this study, we found that knockdown of AOX1 in ovarian cancer cells inhibited cell apoptosis.…”
Section: Discussionmentioning
confidence: 76%
“…For example, loss of AOX1 expression by epigenetic regulation could promote bladder cancer via metabolic deregulations; the SNP rs73055188 of AOX1 locus is related to prostate cancer survival time, and AOX1 gene expression level is correlated with recurrence of prostate cancer [44]. However, the roles for AOX1 in ovarian cancer have not been addressed [45]. In this study, we found that knockdown of AOX1 in ovarian cancer cells inhibited cell apoptosis.…”
Section: Discussionmentioning
confidence: 76%
“…The expression of SH3BP5 is reduced in ovarian cancer samples compared to normal tissue and that silencing of Sab protein expression may lead to chemo-resistance [ 36 ]. The expression of SNTN has high discriminatory power to differentiate between normal tissue, serous borderline ovarian tumors, and serous ovarian carcinoma [ 37 ]. IL22RA2 is highly expressed in various tissues, including those in the female reproductive system [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Expression of SH3BP5 is reduced in ovarian cancer samples compared to normal tissue and that silencing of Sab protein expression may lead to chemo-resistance [35]. Expression of SNTN has high discriminatory power to differentiate between normal tissue, serous borderline ovarian tumors, and serous ovarian carcinoma [36]. IL22RA2 is highly expressed in various tissues including those in the female reproductive system [37].…”
Section: Resultsmentioning
confidence: 99%